Color-tunable light emission of SrLa4-x-ySi3O13:xTb3+, yEu3+ phosphors by energy transfer process for warm white LEDs - Bing Peng; Kaixin Song; Shuangshuang Zhang; Shaohua Shen; Junming Xu; Jun Wu; Weitao Su (AIP Advances, 2018)
SrLa4-x-ySi3O13: xTb3+, yEu3+ phosphor was prepared by high temperature solid-state method. The luminescent centers of Eu3+ and Tb3+ occupying La3+ lattice sites in hosts were confirmed by Rietevld refinement method. The phenomenon of self-cross-relaxation energy transfer is observed between Tb3+ ions from 5D4-7FJ to 7F6-5D4 transition. Additionally, the direction of energy transfer (ET) was observed from Tb3+ to Eu3+ ions, and ET efficiency became more efficient as the concentration of activator increases. The type of ET between Tb3+ and Eu3+ ions was demonstrated to be the dipole-dipole mechanism. The multi-color lights were realized covering the green to red visible region by the route of energy transfer. Furthermore, the decrease of Eu3+ emission intensity resulting from thermal quenching can be effectively compensated by Tb3+→Eu3+ ET. The excellent luminescent properties and thermal stability show this phosphor to be a promising candidate for white LEDs.